The Role of Persuasive Communication in TikTok Content by @taniaanglt to Encourage Generation Z Productivity - Fadhilah Islami, Inayah; Fadillah, Dani (COMMICAST, 2025)
This study aims to analyze the persuasive communication strategies used in TikTok content created by @taniaanglt and to understand how Generation Z audiences process such messages through the central and peripheral routes of the Elaboration Likelihood Model (ELM). Employing a descriptive qualitative design, this research integrates content observation, comment documentation, and in-depth interviews with five informants aged 18–24 years. Data were collected from five selected TikTok videos, public audience comments, and semi-structured interviews, then analyzed using thematic analysis. Findings reveal that visual aesthetics such as pastel color tones, soft lighting, calming music, and slow-paced editing serve as emotional triggers that activate the peripheral route. Once initial emotional engagement is established, reflective narrative statements encourage deeper cognitive elaboration, leading audiences into the central route. The creator’s authenticity further strengthens message credibility and enhances persuasive effectiveness. The study also demonstrates that the interplay between emotional and cognitive pathways fosters productive behavioral changes among Generation Z audiences, including organizing study spaces, adopting realistic daily routines, and embracing balanced productivity practices. Overall, this research confirms that persuasion on short-video platforms works through a synergistic combination of affective and rational processing. It contributes theoretically to expanding the application of ELM in digital media contexts and offers prospects for future studies on persuasive patterns within Generation Z’s online culture.